2009
DOI: 10.1155/2009/190354
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress in Chagas Disease

Abstract: There is growing evidence to suggest that chagasic myocardia are exposed to sustained oxidative stress induced injuries that may contribute to disease progression. Trypanosoma cruzi invasion- and replication-mediated cellular injuries and immune-mediated cytotoxic reactions are the common source of reactive oxygen species (ROS) during acute infection. Mitochondria are proposed to be the major source of ROS in chronic chagasic hearts. However, it has not been established yet, whether mitochondrial dysfunction i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
103
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(107 citation statements)
references
References 85 publications
(100 reference statements)
2
103
0
2
Order By: Relevance
“…Evidence has shown that oxidative stress resulting from augmentation of free radical production plays an important role in the pathogenesis of some heart diseases (Gupta et al 2009). In an experimental model of T. cruzi infection, it was reported that increased oxidative stress and antioxidant insufficiency are associated with myocardial oxidative damage and mitochondrial functional decline, findings that might be of pathological significance in Chagas disease (Wen et al 2004, Gupta et al 2009).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence has shown that oxidative stress resulting from augmentation of free radical production plays an important role in the pathogenesis of some heart diseases (Gupta et al 2009). In an experimental model of T. cruzi infection, it was reported that increased oxidative stress and antioxidant insufficiency are associated with myocardial oxidative damage and mitochondrial functional decline, findings that might be of pathological significance in Chagas disease (Wen et al 2004, Gupta et al 2009).…”
mentioning
confidence: 99%
“…In an experimental model of T. cruzi infection, it was reported that increased oxidative stress and antioxidant insufficiency are associated with myocardial oxidative damage and mitochondrial functional decline, findings that might be of pathological significance in Chagas disease (Wen et al 2004, Gupta et al 2009). …”
mentioning
confidence: 99%
“…However, the increased oxidative damage can also lead to pathophysiological changes that increase in severity along with progression of the disease 3 . In this context, increasing the antioxidant potential of the host's defenses can serve as an intervention strategy for slowing down the progression of Chagas disease.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that T. cruzi infection increases the formation of reactive oxygen species (ROS) by stimulating inflammatory mediators such as cytokines and chemokines, which then leads to oxidative stress in phagocytic cells 3 . ROS and reactive nitrogen species (RNS) have potential to oxidize cellular components such as proteins, lipids, and DNA, leading to morphological deterioration and ultimately cell death in some cases 4 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation